HeartMate 3 implantation via left thoracotomy with descending aortic anastomosis. Issue 7 (18th June 2019) - Kocabeyoglu, Sinan Sabit; Kervan, Umit; Sert, Dogan Emre; Pac, Mustafa
Abstract: Left ventricular assist device implantation through left thoracotomy with outflow anastomosis to the descending aorta is an uncommon approach, particularly in patients with previous sternotomies. However, this approach has certain advantages, such as better surgical outcomes and lower complication rates. Here, we report the technique adapted for HeartMate 3 implantation through left thoracotomy with descending aortic anastomosis.